Distribution and Antibiotic Resistance Profiles of Salmonella enterica in Rural Areas of North Carolina After Hurricane Florence in 2018. (18th February 2021) - Mao, Yuqing; Zeineldin, Mohamed; Usmani, Moiz; Uprety, Sital; Shisler, Joanna L.; Jutla, Antarpreet; Unnikrishnan, Avinash; Nguyen, Thanh H.
Abstract: In this study, water samples were analyzed from a rural area of North Carolina after Hurricane Florence in 2018 and the distribution of the ttrC virulence gene of Salmonella enterica were investigated. We also examined the distribution of culturable S. enterica and determined their antibiotic resistance profiles. Antibiotic resistance genes (ARGs) in the classes of aminoglycoside, beta‐lactam, and macrolide‐lincosamide‐streptogramin B (MLSB) were targeted in this study. The ttrC gene was detected in 23 out of 25 locations. There was a wider and higher range of the ttrC gene in flooded water versus unflooded water samples (0–2.12 × 10 5 copies/L vs. 0–4.86 × 10 4 copies/L). Culturable S. enterica was isolated from 10 of 25 sampling locations, which was less prevalent than the distribution of the ttrC gene. The antibiotic resistance profiles were not distinct among the S. enterica isolates. The aminoglycoside resistance gene aac(6')‐Iy had the highest relative abundance (around 0.05 copies/16S rRNA gene copy in all isolates) among all ARGs. These findings suggested that the 2018 flooding event led to higher copy numbers of the ttrC genes of S. enterica in some flooded water bodies compared to those in unflooded water bodies. The high ARG level and similar ARG profiles were observed in all S. enterica isolates from both flooded and unflooded samples, suggesting that the antibiotic resistance was prevalent in S. enterica within this region, regardless of flooding. Plain Language Summary: In this study, water samples collected from a rural area of North Carolina after Hurricane Florence in 2018 were analyzed. We found that this flooding event increased the copy numbers of the virulence gene ttrC of Salmonella enterica in some flooded water bodies. The antibiotic resistance was prevalent in the S. enterica isolates from different water samples, from both flooded and unflooded areas. Understanding the distribution and antibiotic resistance profiles of S. enterica after a flood event is the first step in understanding how to make farms safe against future flooding and how to treat exposed herds with appropriate antibiotics, securing the food supply chain. Key Points: The ttrC gene of Salmonella enterica was prevalent in several water bodies in a rural area of North Carolina after Hurricane Florence The loads of ttrC gene were high in some, but not all, flooded areas Antibiotic resistance genes were prevalent in the S. enterica isolates in this region